2023
DOI: 10.1172/jci170504
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar epithelial regeneration in the aging lung

SeungHye Han,
G.R. Scott Budinger,
Cara J. Gottardi

Abstract: Advancing age is the most important risk factor for the development of and mortality from acute and chronic lung diseases, including pneumonia, chronic obstructive pulmonary disease, and pulmonary fibrosis. This risk was manifest during the COVID-19 pandemic, when elderly people were disproportionately affected and died from SARS-CoV-2 pneumonia. However, the recent pandemic also provided lessons on lung resilience. An overwhelming majority of patients with SARS-CoV-2 pneumonia, even those with severe disease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 165 publications
(214 reference statements)
0
1
0
Order By: Relevance
“…Quantitative and qualitative changes through age have been documented for some lung progenitor populations. They display different behavior: Basal and club cells decrease in number with age, whereas AT2 cells number remain unchanged but harbor decreased functionality such as self-renewal and differentiation capacity ( Wansleeben et al, 2014 ; Ortega-Martínez et al, 2016 ; Han et al, 2023 ). Moreover, using alveolar organoids, it has been shown that isolated AT2 cells from old mice display a reduced capacity to form alveolar organoids when compared to young adult mice ( Rowbotham et al, 2023 ).…”
Section: What About Aging?mentioning
confidence: 99%
“…Quantitative and qualitative changes through age have been documented for some lung progenitor populations. They display different behavior: Basal and club cells decrease in number with age, whereas AT2 cells number remain unchanged but harbor decreased functionality such as self-renewal and differentiation capacity ( Wansleeben et al, 2014 ; Ortega-Martínez et al, 2016 ; Han et al, 2023 ). Moreover, using alveolar organoids, it has been shown that isolated AT2 cells from old mice display a reduced capacity to form alveolar organoids when compared to young adult mice ( Rowbotham et al, 2023 ).…”
Section: What About Aging?mentioning
confidence: 99%